Necrotizing sialometaplasia of the oral palate: a rare cause of painful mouth ulceration. - BELHAJ, NAJOUA; H.RAHIM,; I.BOUMENDIL,; H.AIT TALEB OUMHANED,; S.NITASSI,; A.OUJILAL,; R.BENCHEIKH,; M.A.BENBOUZID,; L.ESSAKALLI, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Necrotizing sialometaplasia (NMS) is a rare benign inflammatory condition affecting the salivary glands. This pathology mainly affects the accessory salivary glands of the palate. We present a patient who consults for painful bleeding ulcers